Kemampuan Berpikir Kritis dan Metakognisi Siswa dalam Menyelesaikan Masalah Matematika melalui Pendekatan Problem Solving - Muhammad Ikhsan; Said Munzir; Lia Fitria (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The aims of this study are to determine the improvement of critical thinking skills mathematical and metacognition of students who are taught with problem solving approach and the correlation between mathematical critical thinking and metacognition of students. This research is an experimental research with pretest-posttest control group design. The sample this research is the students of class VIII_2 and VIII_3 in SMP Negeri 1 Banda Aceh. Collecting data technique are test and nontest. Data were analyzed using t-test and correlation test. The result of the research shows 1) the critical thinking ability of the students who get the learning through problem solving approach is better than the students who get the conventional learning, 2) Metacognition of students who get the learning by using problem solving approach is better than the students who get the conventional learning, 3) a positive and significant relationship between students' metacognition and critical thinking skills.